Peculiarities of the Legal Regulation of Labor Depending on the Nature of the Employee's Labor Relationship with the Employer and the Place of His/Her Work - Rushana, Orazliyeva (Journal of Innovation in Education and Social Research, 2024)
This article describes the principles of the legal procedure of working on a substitute basis. Also, some aspects of working on a substitute basis are explained.